Depression, Alcohol Misuse, and Suicide Attempt Among North Korean Refugee Women Exposed to Gender-Based Violence - Nam, Boyoung (Journal of interpersonal violence, 2023)
North Korean (NK) refugee women report a disproportionately high rate of suicide compared to the general South Korean (SK) population. NK refugee women’s exposure to gender-based violence (GBV) is a risk factor for adverse mental health symptoms. However, the association between GBV exposure and mental health has received less scholarly attention. This study examined NK refugee women’s exposure to GBV (i.e., sexual violence, human trafficking, and forced sex work) and explored whether it is associated with an increased risk of depression, alcohol misuse, and suicide attempts. A three-way interaction between depression, alcohol misuse, and suicide attempts among GBV-exposed NK refugee women was examined. Data from a snowball sample of 180NK refugee women were analyzed for this study. Findings show that 47.8% experienced GBV in either NK or intermediary countries. Multivariate analyses revealed that depression (OR = 1.13, p < .05) and alcohol misuse (OR = 3.01, p < .01) was significantly associated with suicide attempts in GBV-exposed groups. Results from the three-way interaction (GBV victimization × Depression × Alcohol misuse) suggest that GBV exposure and higher levels of depression were significantly associated with suicide attempts among NK refugee women with greater severity of alcohol misuse (OR = 1.75, p < .05). The findings indicate that NK refugee women with GBV exposure, depression, and alcohol misuse are at increased risk for suicide attempts. Study limitations included the use of snowball sampling and cross-sectional data. This study discusses implications for future research and targeted, trauma-informed treatments focused on GBV and mental health symptoms among NK refugee women.